PERENDAMAN FERMENTASI AIR CUCIAN BERAS DAN GARAM TERHADAP MASA SIMPAN FILET NILA MERAH PADA PENYIMPANAN SUHU RENDAH BERDASARKAN KARAKTERISTIK ORGANOLEPTIK - Shilfana Fitriana; Evi Liviawaty (Universitas Mataram, 2024)
Red tilapia is widely favored by Indonesians due to its resemblance to red snapper in terms of texture and flavor. One of the products made from tilapia is skin-on tilapia fillets, which are known for their high nutritional content, particularly in terms of protein and fat. However, a drawback is that its quality deteriorates rapidly. One approach to minimizing bacterial growth is through the addition of natural preservatives. When salt is added to rice water and allowed to ferment, lactic acid is produced, which possesses antibacterial properties that help slow bacterial growth. This study aims to identify the optimal salt concentration in fermented rice water for extending the shelf life of red tilapia fillets, based on their organoleptic qualities under cold storage conditions (5°-10°C). An experimental method was used, involving four treatments: soaking the tilapia fillets for 30 minutes in fermented rice water with varying salt concentrations (0%, 2%, 3%, 4%) over a 12-day period, with evaluations by five trained panelists. The findings indicated that immersion in fermented rice water influenced the shelf life of red tilapia fillets, as assessed through organoleptic criteria. The fermented solution maintained the aroma, texture, and slime quality until day 9, and preserved the visual appearance until day 10. From these results, it can be concluded that using fermented rice water with a 3% salt concentration is the most effective in preserving the freshness of red tilapia fillets under low-temperature storage (5°C-10°C).